1980
DOI: 10.1007/bf02025936
|View full text |Cite
|
Sign up to set email alerts
|

A modified method for the isolation and determination of brain histamine using Bio-Rex 70

Abstract: Bio-Rex 70, a weak cation exchange resin, has been used to specifically isolate histamine from rat brain tissue. This method compares favourably to other extraction procedures with respect to selectivity, reproducibility and time taken to perform the procedure. However, because it combines the optimum of these properties, it appears more adaptable for routine laboratory use. Following isolation, histamine is quantified fluorometrically after condensation with o-phthaldialdehyde (OPT). The sensitivity of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1980
1980
1987
1987

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…' P Cells Contain Histamine. We detected histamine in P cells, by using a sensitive and selective method (14), at levels of 24-210 ng/10' cells. The level of histamine measured by this technique in a population of resident peritoneal cells from (C57B1/6 x DBA/2)F1 hybrid mice was 330 ng/106 cells, corresponding to a level of7 tug/106 ofthe mast cells present.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…' P Cells Contain Histamine. We detected histamine in P cells, by using a sensitive and selective method (14), at levels of 24-210 ng/10' cells. The level of histamine measured by this technique in a population of resident peritoneal cells from (C57B1/6 x DBA/2)F1 hybrid mice was 330 ng/106 cells, corresponding to a level of7 tug/106 ofthe mast cells present.…”
Section: Resultsmentioning
confidence: 99%
“…Cells were suspended in 0.1 ml of phosphate-buffered saline and boiled for 10 min. Histamine was isolated and assayed spectrophotofluorometrically (14). The procedure was highly selective and sensitive for histamine.…”
mentioning
confidence: 99%
“…For example, noradrenaline (Glowinski & Iversen, 1966) and histamine (Lewis, Fennessy, Laska & Taylor, 1980) have up to a 10 fold difference in the levels determined in the hypothalamus compared to the levels determined in the cerebellum. The wide distribution of prostaglandins without localized concentrations was first reported to occur in dog brain (Holmes & Horton, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…Previous methods have often lacked specificity and have proved too laborious for routine use [9][10][11]. We have recently reported the use of the weak cation exchange resin Bio-Rex 70 in a column chromatographic extraction procedure for the isolation of brain histamine and its subsequent fluorometric quantification following condensation with o-phthaldialdehyde (OPT) [12]. This present study reports the modification of this method for application to the determination of peripheral tissue and fluid levels of histamine.…”
Section: Introductionmentioning
confidence: 93%
“…Although histamine condenses with OPT to produce a fluorophore of strong and stable fluorescence, OPT may form fluorophores with other compounds especially spermidine [13], L-histidine, carnosine (fl-alanyl-histidine) [ 14], histidyl-histidine [ 15], arginine [16] and 5-hydroxytryptamine [ 17]. Prealiminary studies have shown that L-histidine, arginine, carnosine, histidyl-histidine, homovanillic acid and 5-hydroxyindoleacetic acid do not bind to Bio-Rex 70 equilibrated in phosphate buffer at pH 7.5 (for discussion see LEwis et al [12]). Although the amines serotonin, noradrenaline and dopamine bind partially to Bio-Rex 70, these amines produce negligible fluorescence under the assay conditions which produce optimal his~ tamine fluorescence.…”
Section: Introductionmentioning
confidence: 99%